Alkynyl-functionalized gold NHC complexes and their coinage metal clusters12. Issue 30 (14th August 2015) - Kiefer, Claude; Bestgen, Sebastian; Gamer, Michael T.; Lebedkin, Sergei; Kappes, Manfred M.; Roesky, Peter W.
<x xml:space="preserve">Abstract</x> Phenylpropynyl-functionalized N-heterocyclic carbenes as ligands for the synthesis of heterometallic hexanuclear coinagemetal clusters which exhibit mixed metallophillic interactions and intense white photoluminescence at low temperature.